Menggagas Model Pengembangan Manajemen Harta Wakaf Tradisional - Awan Kostrad Diharto (ITB AAS INDONESIA Surakarta, 2019)
Three people issues are: 1) the low quality of education, 2) the cost of increasingly expensive health care, and 3) lack of public welfare, has become a circle of